Soñar en la cárcel. La Liberación de san Pedro interpretada por los pintores en el siglo XVII - Cécile Vincent-Cassy (E-Spania)
The deliverance of Saint Peter is a much rarer episode in Spanish painting than in Italian painting, marked by Rafael Sanzio's interpretation of it in the Chamber of Heliodorus (Vatican). Its rarity has prompted painters to turn their compositions into bravura pieces, demonstrating their ability to deal with the emotional and formal implications of the moment of delivery. The expression of surprise, the breaking of the darkness, the piercing of the angelic light in a closed interior, the non-verbal exchange between Saint Peter and the angel - these are all subjects that Roelas, in a Sevillian unicum of 1612, and then Ribera, responding to a commission from the middle of the Court in 1639, imported from Italy. Alonso Cano, Antonio de Pereda and finally Francisco Rizi vied with each other in their inventiveness to confront the the episode that gave the Apostle Peter his status as Father of the Church.